Biosynthesis, total synthesis, and pharmacological activities of aryltetralin-type lignan podophyllotoxin and its derivatives. Issue 9 (1st August 2022) - Shen, Siyu; Tong, Yuru; Luo, Yunfeng; Huang, Luqi; Gao, Wei
Abstract : This paper mainly focused on the asymmetric synthesis of natural product PTOX by biosynthesis and total synthesis, and pharmacological activities of its derivatives. Abstract : Covering: up to 2022 Podophyllotoxin (PTOX, 1 ), a kind of aryltetralin-type lignan, was first discovered in the plant Podophyllum peltatum and its structure was clarified by W. Borsche and J. Niemann in 1932. Due to its potent anti-cancer and anti-viral activities, it is considered one of the molecules most likely to be developed into modern drugs. With the increasing market demand and insufficient storage of natural resources, it is crucial to expand the sources of PTOXs. The original extraction method from plants has gradually failed to meet the requirements, and the biosynthesis and total synthesis have become the forward-looking alternatives. As key enzymes in the biosynthetic pathway of PTOXs and their catalytic mechanisms being constantly revealed, it is possible to realize the heterogeneous biosynthesis of PTOXs in the future. Chemical and chemoenzymatic synthesis also provide schemes for strictly controlling the asymmetric configuration of the tetracyclic core. Currently, the pharmacological activities of some PTOX derivatives have been extensively studied, laying the foundation for clinical candidate drugs. This review focuses primarily on the latest research progress in the biosynthesis, total synthesis, and pharmacological activities of PTOX and its derivatives, providing a more comprehensive understanding of these widely used compounds and supporting the future search for clinical applications.